Package modular-def: Definition of modular arithmetic

Information

namemodular-def
version1.85
descriptionDefinition of modular arithmetic
authorJoe Leslie-Hurd <joe@gilith.com>
licenseMIT
provenanceHOL Light theory extracted on 2015-04-18
checksum5ae2c622d9003a6de3fab81dc34830b5edd48a21
requiresbase
modular-witness
natural-bits
natural-divides
probability
showData.Bool
Number.Modular
Number.Natural
Probability.Random

Files

Defined Type Operator

Defined Constants

Theorems

modulus mod modulus = 0

0 mod modulus = 0

x. fromNatural (toNatural x) = x

n. n mod modulus < modulus

n. n mod modulus n

x. x 0 = 1

n. toNatural (fromNatural n) = n mod modulus

r. random r = fromNatural (Uniform.random modulus r)

x. ~x = fromNatural (modulus - toNatural x)

n. divides modulus n n mod modulus = 0

n. n < modulus toNatural (fromNatural n) = n

n. n < modulus n mod modulus = n

n. n mod modulus mod modulus = n mod modulus

x y. x - y = x + ~y

x y. x < y toNatural x < toNatural y

x y. x y toNatural x toNatural y

x n. x suc n = x * x n

x1 y1. fromNatural (x1 * y1) = fromNatural x1 * fromNatural y1

x1 y1. fromNatural (x1 + y1) = fromNatural x1 + fromNatural y1

m n. (m mod modulus) * (n mod modulus) mod modulus = m * n mod modulus

m n. (m mod modulus + n mod modulus) mod modulus = (m + n) mod modulus

x y. x < modulus y < modulus fromNatural x = fromNatural y x = y

External Type Operators

External Constants

Assumptions

¬(modulus = 0)

¬

¬

t. t t

p. p

t. t ¬t

(¬) = λp. p

() = λp. p ((select) p)

t. (x. t) t

t. (λx. t x) = t

() = λp. p = λx.

t. ¬¬t t

t. ( t) t

t. (t ) t

t. t

t. t t

t. t

t. t t

t. t

t. t t

t. t

t. t t

t. t

t. ( t) ¬t

t. t ¬t

() = λp q. p q p

t. (t ) (t )

n. 0 < n ¬(n = 0)

x y. x = y y = x

t1 t2. t1 t2 t2 t1

() = λp q. (λf. f p q) = λf. f

n. ¬(n = 0) n mod n = 0

p. ¬(x. p x) x. ¬p x

() = λp. q. (x. p x q) q

m n. m < n m mod n = m

m n. ¬(n = 0) m mod n < n

m n. ¬(n = 0) m mod n m

f g. (x. f x = g x) f = g

() = λp q. r. (p r) (q r) r

t1 t2 t3. (t1 t2) t3 t1 t2 t3

r. (x. y. r x y) f. x. r x (f x)

a b. ¬(a = 0) (divides a b b mod a = 0)

n m. ¬(n = 0) m mod n mod n = m mod n

(∃!) = λp. () p x y. p x p y x = y

e f. ∃!fn. fn 0 = e n. fn (suc n) = f (fn n) n

m n. ¬(n = 0) (m div n) * n + m mod n = m

n m p. ¬(n = 0) (m mod n) * (p mod n) mod n = m * p mod n

n a b. ¬(n = 0) (a mod n + b mod n) mod n = (a + b) mod n